Concrete floors and moisture - Kanare, Howard M., 1953- (Engineering bulletin (Skokie, Ill.), 2008)
Unwanted moisture in concrete floors causes millions of dollars in damage to buildings annually in the United States and Canada. Problems from excessive moisture include deterioration and debonding of floor coverings, trip-and-fall hazards, microbial gowth leading to reduced indoor air quality, staining and deterioration of building finishes. Understanding moisture in concrete leads to design of floors and flooring systems that provide excellent service for many years. This book discusses sources of moisture, drying of concrete, methods of measuring moisture, construction practices, specifications, and responsibilities for successful floor projects.